Exporting, Capital Investment and Financial Constraints - Vlad Manole; Mariana Spatareanu (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
Many firms cite financial constraints as some of the most important impediments to their investment and growth. Using a unique data set from the Czech Republic this paper investigates the importance of financing constraints in the context of exporters. It finds that exporters are less financially constrained than non-exporters. However, after carefully correcting for possible endogeneity and selection issues, the evidence points to less constrained firms self-selecting into exporting rather than exporting alleviating firms' financial constraints. The analysis suggests that easing firms' credit constraints may play an important role in facilitating exporting and that welldeveloped financial markets that would decrease firms' cost of external finance may be needed in order to benefit from selling in foreign markets.
Keywords: F21; F23; F36; 330; exporting; cash flow; financial constraints; Exportindustrie; Verschuldungsrestriktion; Cash Flow; Kapitalkosten; Außenhandelsförderung; Tschechische Republik